(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Language translation plays a vital role in today’s interconnected world. Accurate and efficient translation helps build cultural bridges, supports international business, enhances global education, and fosters communication among diverse societies. This article examines the significance of language translation, modern tools for improving translation, common challenges faced by translators, and how enhanced translation impacts different sectors.